2021
DOI: 10.36283/pjr.zu.10.1/013
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Health Care Providers Regarding Covid-19 in Pakistan

Abstract: This observational study was conducted to assess the attitude, knowledge and practices of health-care providers in context of novel corona virus or COvid-19 in Pakistan. A cross sectional survey has been conducted among the physicians, dentists, physiotherapists, pharmacists and nurses in a number of medical and health related facilities of Pakistan from April to June 2020. A self-constructed questionnaire was used among the 277 health care providers and SPSS version 23 was used to analyze the data. Male parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Second, as a single center cross-sectional study, our findings can only suggest the association of certain risk factors and the prevalence of MRSA carriage and cannot establish any causal relationship. Third, our study questionnaire was modified to meet our local standards and be relevant to our institutional setting and available resources based on established sources, 22,23,24 and it was not formally validated nor was its reliability established. Although the questionnaire was designed to capture comprehensive and relevant information regarding MRSA risk factors and hygiene practices, the possible lack of validity and reliability of the instrument (and consequently our study results), have to be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Second, as a single center cross-sectional study, our findings can only suggest the association of certain risk factors and the prevalence of MRSA carriage and cannot establish any causal relationship. Third, our study questionnaire was modified to meet our local standards and be relevant to our institutional setting and available resources based on established sources, 22,23,24 and it was not formally validated nor was its reliability established. Although the questionnaire was designed to capture comprehensive and relevant information regarding MRSA risk factors and hygiene practices, the possible lack of validity and reliability of the instrument (and consequently our study results), have to be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…During the first wave of COVID-19 infection in Pakistan, a major cross-sectional study including 1,250 Pakistani citizens indicated that 92.3% of the surveyed population had adequate understanding about COVID-19 preventative measures, in contrast to the more severe second wave. 26 According to studies, 70.1% of the public would accept the vaccine if it was available and is suggested by a reliable source. The findings resemble to those of India; where the general public's acceptance of vaccines was determined to be 74%.…”
Section: Vaccine Acceptance Rate: Individuals Inmentioning
confidence: 99%